百度试题 结果1 题目Expand and simplify5(x+5)-4(x-2) 相关知识点: 试题来源: 解析 =5x+25-4x+8=x+33 反馈 收藏
百度试题 结果1 题目(c)Expand and simplify fully(i)4(2y+6)-3(2y-7)8y+24-6y+212y+45(ii)(x -6)(x-4)x^2-6x-4x+24 x^2-10x+24 相关知识点: 试题来源: 解析 8y+ 24-6y+21 2y+45x²-6x-4x +24 x²-10x+ 24 反馈 收藏 ...
Simplify. -4x^{2} - 3x - (x - x^{2} + 3) Simplify the given expression. Express answer with positive exponents. \dfrac{\sqrt{2^{6}x^{2}y^{3}{9x^{-6}y^{3 Simplify the expression completely: ({x^2} / 5)^2 Simplify. ((6 - 3)^2 - 2^2)/(5^3 + (3 - 5)^2) ...
Simplify by removing the factors of 9t^2 + 9t / 36t^2 + 81t. Simplify the expression: {(1-(1 / x))} {(1 - x)}. Simplify ((x^4 )^(-3)) * 2x^4. Simplify 9(x-5)-5(x-2)2x Simplify the polynamial: 4x^2 + 8x - 11x + 6 - 5x^2 + 2. Simplify e^2(2e^4)...
Simplify%20(x−4)2 Go StepsExamples Error:Incomplete Input Equation Examples 5x−6=3x−8 x2−x−6=0 x4−5x2+4=0
解析 Expand ( (x+1/4)(x-3/4)) using the FOIL Method. ( x⋅ x+x(-3/4)+1/4x+1/4(-3/4)) Simplify and combinelike terms. ( x^2+(-3x+x)/4-3/(16)) Add ( -3x) and ( x). ( x^2+(-2x)/4-3/(16)) Simplify each term. ( x^2-x/2-3/(16)) ...
结果1 题目 Simplify the algebraic expression: 5(x + 3)(x − 4) − 3(x − 1)(x − 5) A: 2x= + 13x − 75 B: 8x= − 23x − 45 C: 8x= + 13x − 75 D: 2x= − 23x − 45 相关知识点: 试题来源: 解析 ANone 反馈 收藏 ...
Find y' and simplify. A) y = \sec(x) - x B) y = x^2e^{x^2} C) y = \ln ( \cos(x^3 + 2x +1)) D) y = x^5 - x^4 + x^3 - x^2 + x - 101 Find y' and simplify. x^3 + y^2 = (x^2 + y)^3
1:Expand and simplify (p + 7)(p − 4)2:Simplify 4x3y5 × 3x2y3:Simplify (27q6)3分之2次方:
Simplify (x-2)(x-4i)(x+4i) (x−2)(x−4i)(x+4i)(x-2)(x-4i)(x+4i) Expand(x−2)(x−4i)(x-2)(x-4i)using theFOILMethod. Tap for more steps... (x(x-4i)-2(x-4i))(x+4i) (x⋅x+x(-4i)-2(x-4i))(x+4i) ...